Factors affect account receivable management and its impact on business performance of Vietnamese enterprises - Tran Thi Thanh Tu; Do Ngoc My; Tran Thi Dieu Huong; Tran Minh Anh (My University, 2018)
Factors affect account receivable management and its impact on business performance of Vietnamese enterprises
Keywords: Accounts receivable; Business performance; Vietnam enterprises